Advances in Self‐Assembly of Metabolite Nanostructures: Physiology, Pathology and Nanotechnology. Issue 7 (23rd May 2022) - Shanker Tiwari, Om; Rencus‐Lazar, Sigal; Gazit, Ehud
Abstract: Metabolites are immensely important for the routine function of every cell and take part in numerous physiological processes. Yet, in excess amounts, metabolites can self‐assemble, giving rise to cytotoxic amyloid‐like structures. Such structures may underlie some of the pathological effects associated with inborn error of metabolism disorders characterized by metabolite accumulation due to genetic mutations. Furthermore, such assemblies may have a role in neurodegenerative disorders due to abnormal accumulation. On the other hand, metabolites were shown to form functional assemblies in various organisms. Interestingly, various proteins and peptides showing amyloidal properties also have physiological roles and have been used for the fabrication of functional nanomaterials. Following this notion, metabolite self‐assembly could also be utilized due to several advantages including exceptional biocompatibility, inexpensive production, facile modeling and biodegradability in vivo . Co‐assembly of metabolites resulting in high rigidity can be further used in different biomedical and nanotechnological applications. Metal‐coordinated metabolite assemblies can be used as electrocatalysts in energy harvesting applications. Consequently, the study of metabolite self‐assemblies is not only crucial in order to understand their role in normal physiology and in pathology, but can also uncover a new route in exploring the fabrication of organic, biocompatible structures for material sciences and various technological applications. Abstract : The self‐assembly of functional metabolites opens a new direction in the fabrication of biological and bioinspired materials. This review discusses the various functional metabolite assembled supramolecular structures and their substantial potential in the biomedical and various material science applications.